The cosmic breath : spirit and nature in the Christianity-Buddhism-science trialogue - Yong, Amos. (Philosophical Studies in Science and Religion, 2012)
Recent thinking in the interfaith dialogue and in the theology-science dialogue have taken a "pneumatological turn." The Cosmic Breath explores this pneumatological theology as unfolded in the Christian-Buddhist dialogue alongside critical interaction with the theology-and-science conversation. As an attempt in comparative and constructive Christian philosophical theology, its central thesis is that a pneumatological approach to Buddhist traditions in further dialogue with modern science generates new philosophical resources that invigorate Christian thinking about the natural world and humanity's place in it. The result is a transformation of the Buddhist-Christian dialogue from insights generated in the theology-and-science interface and a contribution to the religion-and-science dialogue from a comparative theological and philosophical perspective.